Are newly exporting firms more innovative? Findings from matched Spanish innovators - Aoife Hanley; Joaquín Monreal-Pérez (Kiel Institute for the World Economy (IfW), 2011)
The prevalence of Internet-based sales by exporters vs. non-exporters is highlighted in a recent World Bank Report (Ferro, 2011) suggesting the use of sophisticated processes when selling overseas. We investigate the count of new process/ product innovations for a group of newly exporting Spanish firms vs. a non-exporter control group. We use propensity score kernel matching and difference-in-differences to help deal with endogenous exporting, sunk exporting costs and common macroeconomic shocks. Our results confirm that selection into exporting is largely driven by productivity and industry technological differences, consistent with exporting sunk costs. We find some evidence of 'technology upgrading' through higher contemporaneous process innovation rates.
Keywords: F14; F23; O3; 330; exporting; innovation; propensity score kernel matching; learning-by-exporting